# Help with homework(rep is awarded)!!

Given that the point with coordinates (1 +&#8730;3 , 5&#8730;3 ) lies on the curve with the equation
y = 22 + px + q,
find the values of the rational constants p and q.
5sqrt(3)
= 2(1 + sqrt(3))^2 + p(1 + sqrt(3)) + q
= 2(4 + 2sqrt(3)) + p(1 + sqrt(3)) + q
= 8 + p + q + sqrt(3) (4 + p)

0 = 8 + p + q
5 = 4 + p

p = 1
q = -9
IZZY!
Given that the point with coordinates (1 +&#8730;3 , 5&#8730;3 ) lies on the curve with the equation
y = 22 + px + q,
find the values of the rational constants p and q.

hi izzy did you mean

y = 2x2 + px + q ?

do i get a rep ?

ther bear
the bear
hi izzy did you mean

y = 2x2 + px + q ?

do i get a rep ?

ther bear

i guess the rep is for the one who does the homework,,, not for the one one gives him the homework again!!!
it was worth a try !!
Worked Solution:

y = 2x2 + px + q

When x=(1+&#8730;3) and y=(5&#8730;3):

5&#8730;3 = 2(1+&#8730;3)² + p(1+&#8730;3) + q
5&#8730;3 = 2(1+&#8730;3)(1+&#8730;3) + p(1+&#8730;3) + q
5&#8730;3 = 2[1+2&#8730;3+3] + p(1+&#8730;3) + q
5&#8730;3 = 2 + 4&#8730;3 + 6 + p + &#8730;3.p + q
5&#8730;3 = 8 + 4&#8730;3 + p + &#8730;3.p + q
5&#8730;3 = &#8730;3(4+p) + 8 + p + q

Equating constants:

5 = 4 + p
p = 1

and:

0 = 8 + p + q

Substitute p:

0 = 8 + 1 + q
0 = 9 + q
q = -9

p = 1, q = -9
i repped the first person to reply. i ll rep again if some1 explains why do you get
5&#8730;3 = &#8730;3(4+p) + 8 + p + q
and then
5 = 4 + p

thanks.
the bear remind me later, like in 2 days and i ll rep u lol.
IZZY!
i repped the first person to reply. i ll rep again if some1 explains why do you get
5&#8730;3 = &#8730;3(4+p) + 8 + p + q
and then
5 = 4 + p

thanks.
the bear remind me later, like in 2 days and i ll rep u lol.

The left hand side must equal the right hand side, as with all equations.

By inspection, it is clear that there is a 'coefficient' for &#8730;3 of 5 on the left hand side. On the right hand side, there is also a 'coefficient' of &#8730;3 of (4+q). These must be equal, so you get:

5 = 4 + p

There is nothing else on the left hand side but still 8 + p + q on the right hand side, so therefore it follows that also:

0 = 8 + p + q
IZZY!
i repped the first person to reply. i ll rep again if some1 explains why do you get
5&#8730;3 = &#8730;3(4+p) + 8 + p + q
and then
5 = 4 + p

thanks.
the bear remind me later, like in 2 days and i ll rep u lol.

it's in my diary !!
IZZY!
like in 2 days and i ll rep u lol.

I don't understand the end bit .

I presume 'rep' means reputation and ' u ' means you : that's easy but what about ' lol.'
steve2005
I don't understand the end bit .

I presume 'rep' means reputation and ' u ' means you : that's easy but what about ' lol.'

I'm fairly sure that 'lol' is supposed to be an abbreviation for 'laugh out loud' though the vast majority of people don't actually laugh at all when they say 'lol'.
Gaz031
I'm fairly sure that 'lol' is supposed to be an abbreviation for 'laugh out loud' though the vast majority of people don't actually laugh at all when they say 'lol'.

Thanks
a Show that
(x2 + 2x &#8722; 3)(x2 &#8722; 3x &#8722; 4) &#8801; x4 &#8722; x3 &#8722; 13x2 + x + 12.
b Hence solve the equation
x4 &#8722; x3 &#8722; 13x2 + x + 12 = 0.

i ve done the a part.i cant do the b part.help is greatly appreciated and will be awarded with rep, if you remind me later.
IZZY!
a Show that
(x2 + 2x &#8722; 3)(x2 &#8722; 3x &#8722; 4) &#8801; x4 &#8722; x3 &#8722; 13x2 + x + 12.
b Hence solve the equation
x4 &#8722; x3 &#8722; 13x2 + x + 12 = 0.

i ve done the a part.i cant do the b part.help is greatly appreciated and will be awarded with rep, if you remind me later.

For part (b) use the result obtained in part (a) and the fact that if f(x)g(x)=0 then f(x)=0 or g(x)=0 (or both).
IZZY!